Curriculum recontextualising using gardens for the health promotion in the life orientation learning area of the senior phase - Jenkins, Msawenkosi Wiseman (Rhodes University, Faculty of Education, Department of Education, 2008)
With a view to understanding how curriculum is interpreted at classroom practice level, the study examined three stories of how the environmental discourse of the National Curriculum Statements (R-9) was recontextualised using school gardens in the Life Orientation Learning Area for the Senior Phase. To understand how the curriculum is recontextualised, I used Bernstein's theory of recontexutalisation where he explained how official pedagogic discourse (OPD) (in this case the environmental discourse is first delocated once it is transferred from the field of production (FOP) and relocated in the recontextualising field (where teacher educators and departmental officials mediate the discourse) and in the field of reproduction (FOR) which is the classroom and school. Bernstein explained that as the discourse is delocated and relocated it undergoes transformation. This transformation is influenced by practitioners' prior-knowledge, experience, culture and beliefs and other factors. To understand how transformation of the environmental discourse takes place, Bernstein's conceptual constructs of selective appropriation and ideological transformation were applied to an interpretation of three lesson processes, to explain how the discourse was changed. Each lesson was reviewed in terms of the selective appropriations and ideological transformations which took place. All three of the lessons observed took place in one school, and as such the study is designed as an interpretive case study where I have tried to make meaning from a rich, thick description of a specific case context. The school is located in Bizana, one of the villages in the O.R. Tambo District Municipality in the Eastern Cape Province,, and is currently in the process of implementing South Africa's new National Curriculum Statement (NCS) like all other schools in South Africa. In conducting the research I observed lessons, interviewed the learners and teachers, and a community member and the manager of the SANBI greening project, and I also analysed documents which included the NCS for Life Orientation, and teachers planning documents and learners work produced in the lessons. I started the study by conducting a document analysis of the NCS, through which I identified dimensions of the Official Pedagogic Discourse. This was used as a framework to review the lessons to understand how the OPD was being recontextualised. The study concludes by discussing the key findings of the study in the form of a set of analytical statements. Some of the findings indicate that teachers have not been given adequate training for understanding and implementing the NCS which affects the recontextualisation process. The study shows that there is a dire need for professional development if the OPD is to be interpreted adequately by teachers so that its implementation at the meso and micro- levels becomes clear and effective.
Keywords: Environmental education -- South Africa -- Eastern Cape -- Case studies; School gardens -- South Africa -- Eastern Cape; Gardening -- Study and teaching (Secondary) -- South Africa -- Eastern Cape; Environmental education -- Curricula -- South Africa -- Eastern Cape; Environmental education -- Curricula -- Case studies; Environmental policy -- South Africa -- Eastern Cape